Evaluation of Enterprise Resource Planning System Maturity with IT-IL V3 Framework at CV. Syntax Corporation Indonesia - Rio Rinaldy; Lena Magdalena; Muhammad Hatta (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to evaluate the development of the Enterprise Resource Planning (ERP) service system at CV. Syntax Corporation Indonesia uses the IT-IL V3 framework, especially in the Service Operations domain. This research is conducted by analyzing the performance and effectiveness of the ERP system that has been implemented, as well as how the system supports the company's daily business operations. Through an IT-IL V3-based evaluation approach, the study assessed critical aspects of ERP service operations such as incident management, problem management, and request management. The findings of this study provide insights into the strengths and weaknesses in the ERP system implementation at the company, as well as recommendations for improvements that can increase efficiency and user satisfaction. Using the IT-IL V3 framework, this study provides practical guidance for better management and development of ERP systems in the future.